The Identity Political Strategy of Legislative Candidates in the 2019 Sidoarjo Regency Pilkada Through Social Media Instagram: Strategi Politik Identitas Caleg di Pilkada Kabupaten Sidoarjo 2019 Melalui Media Sosial Instagram - Rizal, Moch Saiful; Aesthetika, Nur Maghfirah (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe and analyze